Analisis kualitas instrumen tes berbasis etnomatematika pada motif batik Lontara untuk mengukur kemampuan berpikir kritis siswa - Aliyah Nur Fuada Syam; Ahmad Farham Majid; Sitti Mania; Baharuddin Baharuddin (Papanda Journal of Mathematics and Science Research, 2026)
This study aims to analyze the quality of an ethnomathematics-based test instrument on the Lontara Batik motif to measure the critical thinking skills of eighth-grade students. The test instrument consists of 20 multiple-choice questions developed based on Facione’s critical thinking indicators, including interpretation skills, analysis skills, evaluation skills, inference skills, explanation skills, and self-regulation skills, within the context of the Lontara Batik motif. This research employed a quantitative descriptive method with 14 students as participants at one of the MTs in Makassar City. The instrument quality was analyzed in terms of empirical validity, reliability, discriminating power, difficulty level, and distractor effectiveness. The results showed that all test items were valid, with correlation coefficients ranging from 0.551 to 0.886. The instrument demonstrated very high reliability, with a Cronbach’s Alpha value of 0.941. Discriminating power analysis indicated that 19 items were categorized as very good and 1 item as sufficient. In terms of difficulty level, 7 items were classified as easy and 13 items as moderate. Distractor analysis revealed that most distractors functioned effectively, although several options require improvement because they were not selected by the participants. Overall, the Lontara Batik motif-based test instrument was deemed suitable for assessing students’ critical thinking skills. This study contributes to the development of a valid and reliable ethnomathematics-based assessment instrument that integrates local cultural elements to support mathematics learning.